Desarrollo del proceso de atención de enfermería en una paciente de 41 años de edad con diagnostico medico de traumatismo craneoencefálico. - Samaniego Arana, Jhouney Madelaine (2019)
The process nurse is implicit in the development of each one of the activities that meets nursing direct care professional, is also considered as a process systematized, Humanized, that contributes to the needs of the patient, family and environment. By the exposed background, this clinical study is based in developing such a process in a 41 years old patient with diagnosis of traumatic brain injury in the hospital Guasmo Sur. Also, can you say concerning the pathology of the clinical case, that the most frequent cause of brain damage is trauma and traumatic brain injury (TBI) is called. The brain, forming the Central nervous system along with the spinal cord is protected by the skull and includes the brain, the cerebellum and the medulla oblongata. The brain is the most complex structure of the human organism and the main nerve center; its different areas are primarily responsible for the movement, sensations and perceptions, emotions and behavior, and in it, the higher mental functions are held. Damage suffered by the brain after traumatic brain injury is due, on the one hand, to the primary injury (bruise) directly related with the impact on the skull or the rapid movement of acceleration/deceleration, and on the other hand, the injury secondary (edema, hemorrhage, increased pressure in the skull, etc.) which develops as a result of the primary lesion in the first days after the accident, and that can lead to serious consequences in the functional prognosis.